Solitary Lesions on Bone Scintigraphy in Patients with Breast Cancer King Abdulaziz University Medical Centre Experience - Nadia A. Batawil (Journal of King Abdulaziz University: Medical Sciences, 2023)
The discrepancy between bone scintigraphy and computed tomography scanning for solitary bony lesion in patients who have breast cancer is challenging to the referral physician. The purpose of this study was to evaluate the risk of malignancy in solitary lesions on bone scintigraphy in patients who had breast cancer at King Abdulaziz University Medical Centre, and to compare the results between bone scintigraphy and computed tomography scanning. There were 89 patients who had a solitary bone lesion noted on bone scintigraphy and computed tomography performed within 3 months of bone scintigraphy. The solitary bone lesions were benign in 56 (63%) patients and malignant in 33 patients (37%). There were 15 (17%) malignant lesions in bone scan that had initial computed tomography findings that were negative or equivocal for bone metastasis, but all these lesions had destructive changes on follow-up computed tomography scan. In summary, at this medical center the frequency of malignancy is high (37%) in solitary bone lesions in patients who have breast cancer, regardless of appearance of the lesion on an initial computed tomography scan. Prospective study with a larger group of patients is recommended.